Cultural intelligence, global mindset, and cross-cultural competencies: a systematic review using bibliometric methods. (31st January 2020) - Yari, Nooria; Lankut, Erik; Alon, Ilan; Richter, Nicole Franziska
We conducted a systematic review of 158 publications on Cultural Intelligence (CQ) and related concepts, Global Mindset (GM), and Cross-cultural Competence (CC) using bibliometric methods. We apply citation analysis to highlight the most influential (in terms of citations) journals, publications, and specific researchers in the field. We apply factor and cluster analyses to analyse co-citations to identify the current knowledge structure in the research field. With content coding on the resulting groups of co-citations, we identify five research streams showing the overlap between the CQ, GM, and CC constructs, and also revealing the separations in the research on the constructs. We perform burst analyses to identify trends and emerging topics or streams. Building on this, we outline future research opportunities.